Remote education in the university context: necessary collaborative work for teaching pedagogical mediation in the time of COVID - Cerdas-Montano, Virginia (2020)
The Curricular Commission of the Division of Education for Work. Assumes the modality of remote education through collaborative work, supporting the teaching staff in the development of required skills for the teaching and learning processes.